2021
DOI: 10.1186/s42522-021-00040-z
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous anthrax outbreak associated with handling dead animals, Rhino Camp sub-county: Arua District, Uganda, January–May 2018

Abstract: Background On 18 January 2018 a 40 year old man presented with skin lesions at Rhino Camp Health Centre. A skin lesion swab was collected on 20 January 2018 and was confirmed by PCR at Uganda Virus Research Institute on 21 January 2018. Subsequently, about 9 persons were reported to have fallen ill after reporting contact with livestock that died suddenly. On 9 February 2018, Arua District notified Uganda Ministry of Health of a confirmed anthrax outbreak among humans in Rhino Camp sub-county. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…44,45 This limitation is not uncommon in other anthrax studies when the cases were reported late, hindering timely sample collection and pathogen detection. 46,47 CONCLUSION Here, we provide the spatial and spatiotemporal epidemiology of anthrax in humans and livestock in Ha Giang province, northern Vietnam. These findings directly inform One Health surveillance and the response of provincial authorities in better controlling anthrax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 This limitation is not uncommon in other anthrax studies when the cases were reported late, hindering timely sample collection and pathogen detection. 46,47 CONCLUSION Here, we provide the spatial and spatiotemporal epidemiology of anthrax in humans and livestock in Ha Giang province, northern Vietnam. These findings directly inform One Health surveillance and the response of provincial authorities in better controlling anthrax.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 This limitation is not uncommon in other anthrax studies when the cases were reported late, hindering timely sample collection and pathogen detection. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…These factors were present most likely influencing the anthrax outbreak in both animals and humans. Previous investigations of outbreaks in Uganda that have been done recently also found the association of anthrax to handling of meat from animals that died suddenly [ 4 , 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contact with livestock included skinning, slaughtering, carrying meat and cleaning the carcasses of the animals. These are mainly male-dominated roles which explains why males are usually the most affected sub-population during anthrax outbreaks [ 4 , 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation